Two-dimensional lithium diffusion behavior and probable hybrid phase transformation kinetics in olivine lithium iron phosphate. Issue 1 (December 2017) - Hong, Liang; Li, Linsen; Chen-Wiegart, Yuchen-Karen; Wang, Jiajun; Xiang, Kai; Gan, Liyang; Li, Wenjie; Meng, Fei; Wang, Fan; Wang, Jun; Chiang, Yet-Ming; Jin, Song; et al.
Abstract Olivine lithium iron phosphate is a technologically important electrode material for lithium-ion batteries and a model system for studying electrochemically driven phase transformations. Despite extensive studies, many aspects of the phase transformation and lithium transport in this material are still not well understood. Here we combineoperando hard X-ray spectroscopic imaging and phase-field modeling to elucidate the delithiation dynamics of single-crystal lithium iron phosphate microrods with long-axis along the [010] direction. Lithium diffusivity is found to be two-dimensional in microsized particles containing 3% lithium-iron anti-site defects. Our study provides direct evidence for the previously predicted surface reaction-limited phase-boundary migration mechanism and the potential operation of a hybrid mode of phase growth, in which phase-boundary movement is controlled by surface reaction or lithium diffusion in different crystallographic directions. These findings uncover the rich phase-transformation behaviors in lithium iron phosphate and intercalation compounds in general and can help guide the design of better electrodes. Lithium transport and phase transformation kinetics in olivine LiFePO4 electrode remain not fully understood. Here the authors show that microsized olivine particles possess 2D lithium diffusivity and exhibit a possible hybrid mode of phase boundary migration upon cycling.